Antiproliferative Activity Evaluation of a Series of N-1,3-Benzothiazol-2-ylbenzamides as Novel Apoptosis Inducers - Filomena Corbo; Alessia Carocci; Domenico Armenise; Nicolino De Laurentis; Antonio Laghezza; Fulvio Loiodice; Patrizia Ancona; Marilena Muraglia; Vincenzo Pagliarulo; Carlo Franchini; Alessia Catalano (Journal of Chemistry)
A series of N-1,3-benzothiazol-2-ylbenzamide derivatives were studied for their antiproliferative activity on human liver hepatocellular carcinoma (HepG2) and human breast cancer (MCF-7) cell lines. Most of them were found to show a prominent inhibitory effect on cell growth. Among the most active compounds, 1k emerged for its proapoptotic effect that is particularly evident towards MCF-7 cancer cell lines.